2018
DOI: 10.15580/gjee.2018.1.052418074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Processing Methods on the Chemical Compositions of Mucuna pruriens Leaves

Abstract: The study was to evaluate the effects of different processing methods on the proximate and anti-nutritional contents of Mucuna pruriens leaf meal. The Mucuna pruriens leaves were collected and processed by Air-dried Mucuna Leaf Meal (AMLM), Soaked Mucuna Leaf Meal in Cold Water (CMLM), Soaked Mucuna Leaf Meal in Hot Water (HMLM) and Fermented Mucuna Leaf Meal (FMLM). Proximate analysis showed that FMLM had the highest value (25.94±0.94%), while the lowest recorded in the CMLM (23.00±0.00%). The analysis of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The experiment was conducted in the Fisheries Laboratory, Department of Forestry and Fisheries, Kebbi State University of Science and Technology Aliero, Kebbi State Nigeria. Aliero is located in the Southeast of Kebbi State between approximate longitudes 3 0 6ꞌE to 4 0 27ꞌE and latitudes 11 0 03ꞌN to 12 0 47ꞌN (Singh, 2013;Ibrahim et al, 2018).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The experiment was conducted in the Fisheries Laboratory, Department of Forestry and Fisheries, Kebbi State University of Science and Technology Aliero, Kebbi State Nigeria. Aliero is located in the Southeast of Kebbi State between approximate longitudes 3 0 6ꞌE to 4 0 27ꞌE and latitudes 11 0 03ꞌN to 12 0 47ꞌN (Singh, 2013;Ibrahim et al, 2018).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The experiment was conducted in the Fisheries Laboratory, Department of Forestry and Fisheries, Kebbi State University of Science and Technology Aliero, Kebbi State Nigeria. Aliero is located in the Southeast of Kebbi State between approximate longitudes 3 0 6ꞌE to 4 0 27ꞌE and latitudes 11 0 03ꞌN to 12 0 47ꞌN (Singh, 2013;Ibrahim et al, 2018).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…One kilogram of Mucuna pruriens leaves was fermented (FMLM) with 2 grams of yeast (Saccharomyces cerevisiae) in an airtight container for 72 hours at room temperature according to the method reported by Padmavathy and Shobha, [12] and used by Ibrahim et al [11]. The clean beans were toasted for about 15 minutes and then de-hulled, followed by winnowing, milling and sieving [13].…”
Section: Feed Stuff and Feed Formulationmentioning
confidence: 99%
“…Mucuna pruriens belongs to the family Fabaceae and has been described as a multipurpose plant which is used extensively both for its nutritional and medicinal properties [10]. Ibrahim et al [11] has reported the information on the effects of different processing methods on the proximate and anti-nutritional contents of M. prurien leaf meal, and concluded that fermented M. pruriens leaf meal has a potential to be utilised as a source of protein and energy for animals. There is, however, no information on the utilisation of fermented M. pruriens leaf meal in the diets of Clarias gariepinus fingerlings.…”
Section: Introductionmentioning
confidence: 99%